Development Of Online Apartment Management System - Ali, Siti Haryani; Azmi, Hafizuddin (Journal of Computing Technologies and Creative Content, 2017)
Although there are various services provided by the management of the apartment to the residents, there are still deficiencies found in the way the services operated resulting in the problems faced by the residents as well as the management itself. The aim of this project is to develop an Online Apartment Management System, by which the management of apartment may manage and perform their operations online. The apartment administration will benefit from this system as they can manage all transactions made by users online and paperless. The system’s interface is developed using PHP language by using the Dev-PHP software and the system’s database was created using MySQL database. The system’s features include paying bills, purchasing car stickers, complaints submissions, and update the tenants information online, making it more effective, efficient, interactive and successfully solve the problems faced compared to using the current system.